Identification of cells of the human mononuclear phagocyte system with rat monoclonal antibodies. - Aqel, N; Clark, M; Jones, D; Arno, J; Waldmann, H (1987)
Five rat monoclonal antibodies (McAbs) to human macrophages are described: YTH 8.18, YTH 25.7, YTH 51.1, YTH 85.12.1, and YHB 65.5. These McAbs are divided into three groups, since YTH 8.18, YTH 51.1, and YHB 65.5 are thought to identify the same antigen. These McAbs react with some bone marrow blast cells, granulocytes, and different percentages of peripheral blood monocytes. When studied on different body tissues, they were found to identify all members of the mononuclear phagocyte system (MPS), except Langerhans cells of skin and epithelium and in the case of one group (YTH 8.18/YTH 51.1/YHB 65.5) osteoclasts. In nine reactive lymph nodes the anti macrophage McAbs identified germinal centre macrophages, sinus macrophages, and interdigitating cells, but not dendritic reticulum cells. They also identified epithelioid macrophages and Langhans-type multi-nucleated giant cells in lymph nodes involved in granulomatous lesions (sarcoidosis and toxoplasmosis). In 24 cases of non-Hodgkin's lymphoma, the antimacrophage McAbs identified reactive macrophages in cases of B- or T-lymphocyte origin, whereas in three selected cases of true histiocytic lymphoma all the McAbs were found to be reactive with the vast majority of neoplastic macrophages as they were with the cells of a neoplastic macrophage line (U937). The possible use of these McAbs in the identification of benign and malignant macrophages in different systems is discussed.